2021
DOI: 10.3389/fimmu.2020.609689
|View full text |Cite
|
Sign up to set email alerts
|

Local Stabilization of Hypoxia-Inducible Factor-1α Controls Intestinal Inflammation via Enhanced Gut Barrier Function and Immune Regulation

Abstract: Intestinal epithelial cells are adapted in mucosal hypoxia and hypoxia-inducible factors in these cells can fortify barrier integrity to support mucosal tissue healing. Here we investigated whether hypoxia-related pathways could be proposed as potential therapeutic targets for inflammatory bowel disease. We developed a novel hypoxia-inducible factor (HIF) prolyl hydroxylase inhibitor, CG-598 which stabilized HIF-1α in the gut tissue. Treatment of CG-598 did not affect extra-intestinal organs or cause any signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 65 publications
0
25
0
Order By: Relevance
“…Hypoxia leading to hypoxia-inducible factor (HIF)-signaling pathway activation is a common feature of inflammatory diseases, including IBD ( Kerber et al, 2020 ). HIF-1 α is protective in IBD models ( Kim et al, 2021 ), and HIF-2 α is essential in maintaining the immune response and regenerative capacity of the intestinal epithelium in IBD ( Ramakrishnan and Shah, 2016 ). At the same time, HIF-2 α but not HIF-1 α constitutive activation leads to IBD development or exacerbation in colitis models ( Xue et al, 2013 ; Solanki et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Hypoxia leading to hypoxia-inducible factor (HIF)-signaling pathway activation is a common feature of inflammatory diseases, including IBD ( Kerber et al, 2020 ). HIF-1 α is protective in IBD models ( Kim et al, 2021 ), and HIF-2 α is essential in maintaining the immune response and regenerative capacity of the intestinal epithelium in IBD ( Ramakrishnan and Shah, 2016 ). At the same time, HIF-2 α but not HIF-1 α constitutive activation leads to IBD development or exacerbation in colitis models ( Xue et al, 2013 ; Solanki et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have also shown that genetic deletion of PHD-1 in murine models of dextran sulfate sodium (DSS) -induced colitis protected against disease (26). Furthermore, various pharmacological compounds that influence the HIF pathway have demonstrated a protective role in murine models of colitis, and in suppression of disease associated inflammation (27)(28)(29)(30). Thus, one possible interpretation of our data is that some of these findings cited above of an anti-inflammatory role for HIF may be due to a HIF-regulated myeloid cell suppression of T cell-induced or -dependent tissue damage.…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia has also been studied in the context of IBD, and several studies showed that hypoxia inducible factor 1 subunit alpha (HIF-1α) inhibitors improve intestinal barrier function when administered orally [ 129 ] or intraperitoneally [ 130 ]. miR-135a was found to be suppressed in both UC and CD patients [ 86 ].…”
Section: Microrna As a Therapeutic Target In Ibdmentioning
confidence: 99%